Functional Interfaces in Pure and Blended Oxide Nanoparticle Networks: Recombination versus Separation of Photogenerated Charges - Siedl, Nicolas; Elser, Michael J.; Bernardi, Johannes; Diwald, Oliver (Journal of Physical Chemistry C, 2009)
Solvent-mediated particle aggregation was employed to produce nanoparticle networks containing a high abundance of functional interfaces. Using electron paramagnetic resonance spectroscopy (EPR), we experimentally observed that the intentional attachment of vapor-grown ZrO_2 nanocrystals to TiO_2 particle surfaces yields networks of intermixed nanoparticles with substantially improved charge separation properties. The superior performance holds also in comparison to homogeneous ZrO_2 and TiO_2 nanoparticle networks that exhibit a higher charge recombination loss in comparison to powders of unconnected nanocrystals.
EAM Import::2019-03-14